1992
DOI: 10.1002/cber.19921250616
|View full text |Cite
|
Sign up to set email alerts
|

Hexasilylbenzene, C6(SiH3)6

Abstract: The title compound was obtained in a four-step synthesis start-central benzene ring intact. LiAIHl reduction of the resulting ing from (4-methoxypheny1)silane. Owing to the presence of hexakis[(trifluoromethylsulfonyloxy)silyl]benzene (5) finally activating p-methoxy groups in the key intermediate hexa-leads to crystalline, sublimable, air-stable C6(SiH3j6 (S), m.p. kis[(4-methoxyphenyl)silyl]benzene (4), the peripheral aryl 165°C. In the crystals (triclinic, space group Pi) the structure groups can be cleaved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
3

Year Published

1994
1994
2000
2000

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 10 publications
4
14
0
3
Order By: Relevance
“…The ease of replacement of Y by OTf decreases in the order (Y substituent) of NEt 2 [41][42][43][44] Phenylsilanes, which are highly reactive towards the protodesilylation reaction, are ideal starting materials for the synthesis of novel silyl triflates. Eaborn and coworkers 45 studied the effects of the substituents Z on the rate of acid cleavage of p-Z-C 6 H 4 SiR 3 (Scheme 1) and found that the reaction rates fell significantly in the order (Z substituent) of OCH 3 …”
Section: Resultsmentioning
confidence: 99%
“…The ease of replacement of Y by OTf decreases in the order (Y substituent) of NEt 2 [41][42][43][44] Phenylsilanes, which are highly reactive towards the protodesilylation reaction, are ideal starting materials for the synthesis of novel silyl triflates. Eaborn and coworkers 45 studied the effects of the substituents Z on the rate of acid cleavage of p-Z-C 6 H 4 SiR 3 (Scheme 1) and found that the reaction rates fell significantly in the order (Z substituent) of OCH 3 …”
Section: Resultsmentioning
confidence: 99%
“…All attem pts to obtain l,2,4,5-tetra(silyl)benzene gave only the disilylated species with two of the four halogen atoms of the starting material remaining in the product. This result is surprising since the structural situation appears to be very similar for each substitution step in 1,2-dibromo-and in 1,2,4,5-tetrabromo-benzene, and also since even complete substitution was possible in hexachlorobenzene (to give hexa(silyl)benzene) [13], The structural data for 4 and 6 give no indication of any steric congestion, which could make steric ef fects responsible for the failure of the synthetic work. The orientation of the tolyl groups is also such that no covering of the reaction center is ex pected.…”
Section: Discussionmentioning
confidence: 94%
“…Depending on the substitution pattern of the monomers, different kinds of cross-linking are to be expected, which are leading to simple oligomers, rings, chains, or polydimensional networks [1]. Simple poly(silyl)-arenes bearing solely hydrogen at the silicon sub stituents were largely unknown until some very re cent studies, which have shown the way to at least a few of the possible poly(silyl)benzenes and their isomers [2], Following our own work on poly(silyl)alkanes [3][4][5][6][7], -alkenes [8][9][10], -alkynes [11,12], and -arenes [12], including hexa(silyl)benzene [13] and l,8-di(silyl)naphthalene [14], we now report the first synthesis of the title compounds, the silicon analogue of o-xylene and one of its brom inated derivatives.…”
mentioning
confidence: 99%
“…Die Darstellung von Silyltriflaten durch Spaltung verschiedener Silicium-Element-Bindungen in Monosilanen mittels Trifluormethansulfonsäure wurde von Bassindale [43], Schmidbaur [44,45] und im eigenen Arbeitskreis [46 -50] …”
Section: Synthese Von Silyltriflatenunclassified